The interiors of Uranus and Neptune: current understanding and open questions. (25th December 2020) - Helled, Ravit; Fortney, Jonathan J.
Abstract : Uranus and Neptune form a distinct class of planets in our Solar System. Given this fact, and ubiquity of similar-mass planets in other planetary systems, it is essential to understand their interior structure and composition. However, there are more open questions regarding these planets than answers. In this review, we concentrate on the things we do not know about the interiors of Uranus and Neptune with a focus on why the planets may be different, rather than the same. We next summarize the knowledge about the planets' internal structure and evolution. Finally, we identify the topics that should be investigated further on the theoretical front as well as required observations from space missions. This article is part of a discussion meeting issue 'Future exploration of ice giant systems'.